Trend of Dengue Cases in Ecuador during the First Quarter of 2024 - Ariel Antonio Torres Rodriguez*; Martha Maria Fors Lopez; Erik Renato Leon Zapata (Archives of Community Medicine and Public Health, 2025)
Abstract A retrospective cross-sectional descriptive study was conducted with the aim of describing the current situation of Dengue in Ecuador in the first quarter of 2024 and demonstrating the presence of an outbreak due to the significant increase in the number of cases. No sample calculation was performed as 100% of patients diagnosed with Dengue in the study period were used; 3 variables were addressed: frequency of cases, severe cases, and deaths, proportion statistics such as rate and percentage were used, and linear regression was used for trends. The study was extended to cases with warning signs to further visualize the alert situation in the country. The results showed a significant increase in cases in the context of a dengue outbreak in Ecuador, generating a warning of a significant increase in cases and a projection of an increasing number of cases in the coming years. Promoting the need to strengthen dengue control and prevention actions in the country.